Next Move : Contemporary Art from Thailand. - Huangfu, Binghui; Poshyananda, Apinan; Gaweewong, Gridthiya; Lenzi, Iola; Rodboon, Somporn; Knithichan, Khetsirin; Ng, Josef; Earl Lu Gallery, LASALLE-SIA College of the Arts, Singapore (Singapore : Lasalle-Sia College of Arts, 2003)
Shoawanasai, Michael ; Phunsombatlert, Bundith ; Puipia, Chatchai ; Phaosavasdi, Kamol ; Sriwanichpoom, Manit ; Shaowanasai, Michael ; Toemsombat, Montri ; Utarit, Natee ; Nuts Society ; Sanpitak, Pinaree ; et al.
Earl Lu Gallery, Lasalle-Sia College of Arts, Singapore, 7 March - 27 April 2003
kunstcatalogus
Keywords: Thailand